Effects of one-step and three-step run-up on kinematic parameters and the efficiency of jump shot in handball - Belcic, I.; Ocic, M.; Dukaric, V.; Knjaz, D.; Zoretic, D. (Applied Sciences, 2023)
The main aim of this research is to analyse the kinematic model of two different variations of executing the jump shot, one performed after one step in the preparation phase and the other performed after a three-step preparation phase (run-up). Respondents (N = 27) are female Croatian national handball team players (U17 and U19). After basic anthropometric and morphological measurements, along with the warmup, respondents proceeded to shoot with one- and three-step shots directed at targets in the upper and lower opposite corner of the goal. A significant difference was found in all measured kinematic parameters between one- and three-step jump shots: hand velocity (p < 0.001 for the upper opposite (UO) and p < 0.001 for the lower opposite target (LO)); hand height reached (p < 0.05 UO and p < 0.01 LO); jump height (p < 0.001 UO and p < 0.001 LO); shoulder velocity (p < 0.001 UO and p < 0.001 LO); and ball velocity (p < 0.05 UO and p < 0.01 LO). Coaches should incorporate specific jump shots after one step to automate this movement and produce the best shooting technique, which will allow them to have smaller differences or no differences between techniques with three-steps and one-step jump shots. Consequently, this will lead to better performance indicators which consist of shooting on target from various positions in the field.